Customized agile development process for embedded software development - Juhola, Tomi (fi=Turun yliopisto|en=University of Turku|, 2010)
Agile software development has grown in popularity starting from the agile manifesto declared in 2001. However there is a strong belief that the agile methods are not suitable for embedded, critical or real-time software development, even though multiple studies and cases show differently. This thesis will present a custom agile process that can be used in embedded software development. The reasons for presumed unfitness of agile methods in embedded software development have mainly based on the feeling of these methods providing no real control, no strict discipline and less rigor engineering practices. One starting point is to provide a light process with disciplined approach to the embedded software development. Agile software development has gained popularity due to the fact that there are still big issues in software development as a whole. Projects fail due to schedule slips, budget surpassing or failing to meet the business needs. This does not change when talking about embedded software development. These issues are still valid, with multiple new ones rising from the quite complex and hard domain the embedded software developers work in. These issues are another starting point for this thesis. The thesis is based heavily on Feature Driven Development, a software development methodology that can be seen as a runner up to the most popular agile methodologies. The FDD as such is quite process oriented and is lacking few practices considered commonly as extremely important in agile development methodologies. In order for FDD to gain acceptance in the software development community it needs to be modified and enhanced. This thesis presents an improved custom agile process that can be used in embedded software development projects with size varying from 10 to 500 persons. This process is based on Feature Driven Development and by suitable parts to Extreme Programming, Scrum and Agile Modeling. Finally this thesis will present how the new process responds to the common issues in the embedded software development. The process of creating the new process is evaluated at the retrospective and guidelines for such process creation work are introduced. These emphasize the agility also in the process development through early and frequent deliveries and the team work needed to create suitable process.